Light-controlled cooperative catalysis of asymmetric sulfoxidation based on azobenzene-bridged chiral salen TiIV catalysts. Issue 44 (29th April 2020) - Fu, Wenqin; Pi, Yibing; Gao, Mengqiao; Wang, Weiying; Li, Chaoping; Tan, Rong; Yin, Donghong
Abstract : Azobenzene-bridged chiral salen Ti IV catalysts enabled the cooperative bimetallic catalysis of asymmetric sulfoxidation in a light-controllable way through the E / Z photoisomerism of an azobenzene linker. Abstract : Incorporation of azobenzene into the linker of bimetallic chiral salen Ti IV catalysts allowed the photoswitchable arrangement of the two Ti(salen) units through cis / trans photoisomerization of azobenzene. The differently arranged Ti(salen) units changed their cooperative function to reflect the positional relationships, as a result, their efficiency as cooperative catalysts in asymmetric sulfoxidation could be readily controlled by light stimuli.